Young Sun, galactic processes, and origin of life. (15th October 2020) - Obridko, Vladimir N.; Ragulskaya, Maria V.; Khramova, Elizaveta G.
Abstract: The paper deals with the dynamics of the young Sun, physical conditions in the early Solar System and on the Earth. An extended interpretation of the faint young Sun paradox and its possible solutions are proposed. Various hypotheses are discussed including their advantages and disadvantages. The faint young Sun paradox follows from the Standard Solar Model with the conservation of mass condition. However, the mass of the Sun did not remain constant during its evolution. It was steadily decreasing, mainly in the first 2–2.5 billion years. But even with the most optimistic estimates, the uneven loss of mass during the evolution of our star is unable to fully compensate for the lack of luminosity reaching the surface of the early Earth. The primary biosphere had to search for alternative — e.g., radiation, chemical or geothermal — sources of energy. The prevalent configurations of solar magnetic fields also changed in the course of evolution, the strong quadrupole fields dominating at the early stages. At the age of about 2–2.5 billion years and the rotation period of about 15 days, the dipole magnetic field with large mass outflow from coronal holes begins to dominate, and the steady solar wind becomes the main mechanism of mass loss in the Sun in the following two billion years. The activity of the early Sun was much higher than it is today. The high-frequency (gamma-, X-ray, and UV) radiation, radio emission, coronal mass ejections, and solar cosmic rays exceeded the present-day values by 2–3 orders of magnitude. The article emphasizes the role of the dynamics of the young Sun, cosmic rays, magnetic field and other protective shells of the Earth as factors determining the occurrence, selection, and development of the first living systems.